PENINGKATAN PERKEMBANGAN SOSIAL EMOSIONAL ANAK MELALUI KEGIATAN MERONCE - Ainin Ditya; Khadijah; Amirah Syarifah Sirait; Najwa Mahfuza; Putri Puspita Hasri (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
This research highlights the positive impact of using bead stringing teaching materials in play-based learning activities on the social-emotional development of children. Engaging children in bead stringing activities leads to increased interest, independence, ability to follow rules, task completion, and appreciation of their own and others' work. The enjoyable environment created motivates children to participate with enthusiasm and focus, while also developing patience and perseverance. The research methodology employs a qualitative approach with in-depth interviews and observations to explore the effectiveness of bead stringing activities in promoting children's social-emotional development and identifying influencing factors. From the research findings, bead stringing activities not only contribute to artistic and creative development but also play a crucial role in developing essential social and emotional skills for the holistic growth and development of young children. Therefore, the use of bead stringing activities in early childhood education can be considered as an effective method to support children's social-emotional development.